A review on electric two wheelers - Syazwana, Sapee; Daing Mohamad Nafiz, Daing Idris; Ahmad Fitri, Yusop; F., Basrawi; Azri Hizami, Rasid; Muhammad Hadi, Hassan; Jiang, X. X. (EDP Sciences, 2018)
South East Asian cities such as Kuala Lumpur, Jakarta and Bangkok rely heavily on motorcycles. A huge number of urban residents depend on motorcycles for all types of activities such as working, ridehailing and delivery services, going to school or leisure. According to Malaysia Automotive Association (MMA) statistics, there are about 13 million registered motorcycles in Malaysia as of August 2017. The pollutants that a four-stroke-engine 50 cc motorcycle emits per kilometre are usually much higher than a 2-litre passenger car; 2.7 times higher for CO and 6.7 times higher for HC and NOX. Controlling excessive air pollution and emissions levels generated by the use of a motorcycle is one of the keys to improving air quality. Electric two-wheelers have been well adopted in Asia Pacific countries like China and Taiwan. This paper provides extensive review and analysis on development history, environmental and mobility impacts, challenge and limitation of electric two-wheelers from around the world and the potential of its emergence in Malaysia.